My question refers to the following equations:
(The summation over $\gamma$ is described here: Summation over a product of binomial coefficients)
When I perform the substitution $\beta=\alpha-\lambda+\mu+\sigma$, write everything as factorials and collect the terms again I arrive at eq. (3.13), except that my summation starts from $\beta=\sigma+\mu-\lambda$.
How do they end up with the sum starting from $\beta=0$?
(Remarks: all variables are integers, $\sigma,\lambda,\mu\geq 0$, $\lambda\geq\mu$)